Overexpression of the HcPT1.1 transporter in Hebeloma cylindrosporum alters the phosphorus accumulation of Pinus pinaster and the distribution of HcPT2 in ectomycorrhizae - Amenc, Laurie; Becquer, Adeline; Trives-Segura, Carlos; Zimmermann, Sabine D.; Garcia, Kevin; Plassard, Claude (Frontiers in Plant Science, 2023)
Ectomycorrhizal (ECM) fungi associate with the roots of woody plants in temperate and boreal forest, helping them to acquire water and nutrients. The molecular mechanisms responsible for these nutritional transfers are still poorly understood. The ECM fungus Hebeloma cylindrosporum expresses three H+:Pi symporters (HcPT1.1, HcPT1.2, and HcPT2) in extraradical and intraradical hyphae of ectomycorrhizae to transport phosphorus (P) from the soil to colonized roots. Since HcPT1.1 is only upregulated under low P conditions, we wondered whether an artificial overexpression of this transporter by a fungal Agrotransformation strategy could result in better P nutrition of the host plant Pinus pinaster. Surprisingly, we demonstrated that plants interacting with transgenic fungal lines overexpressing HcPT1.1 did not accumulate more P in their shoot compared to plants colonized with control isolates. Although the overexpression of HcPT1.1 did not affect the expression level of the other two P transporters in pure culture, a strong reduction of HcPT2 proteins in ectomycorrhizae, particularly in the hyphae internally colonizing roots, was observed by an immunolocalization approach. Our results revealed that the artificial overexpression of the P transporter HcPT1.1 strongly decreased the distribution of HcPT2 proteins in symbiotic structures, but still improved the P status of the host plant shoots compared to non-mycorrhizal plants. This suggests that a tight regulation and a functional redundancy between the H+:Pi symporters of H. cylindrosporum might exist to ensure a sustainable P delivery to P. pinaster roots.